Sidr Honeys Physical and Chemical Characterization, a Comprehensive Approach through LC-MS/MS, NMR, and GC-MS Analysis - Aida A. Abd El-Wahed; Eman H. Rashwan; Mohamed F. AlAjmi; Shaden A. M. Khalifa; Aamer Saeed; Chao Zhao; Yahya Al Naggar; Zhiming Guo; Syed G. Musharraf; Kai Wang; Hesham R. El-Seedi; Nermeen Yosri (Separations, 2023)
Honey intake is advantageous to human health due to its antioxidant, anticancer, anti-inflammatory, and antimicrobial properties, all of which are attributed to the rich bioactive compound contents. Moreover, hepatoprotective, wound healing, and gastrointestinal protective properties have been documented. Honey’s nutritional value is significantly affected by its chemical composition, which varies depending on botanical and geographical origin. In particular, after Manuka honey, Sidr honey from the Ziziphus species is the most popular. The chemical compositions, physicochemical properties, bioactive compounds, and sensory characteristics of two Sidr honey samples from Egypt and Saudi Arabia were investigated in the current study. Moisture content, electrical conductivity (EC), pH, free acidity (FA), total acidity, lactone hydroxymethylfurfural (HMF) content, and diastase (α-amylase) activity were measured. By using high-performance liquid chromatography (HPLC), mass spectrometry (LC-MS/MS), nuclear magnetic resonance (1HNMR), and solid-phase micro-extraction (SPME) coupled with gas chromatography (GC-MS) analyses, the sugar profile, non-volatile, and volatile compounds were also identified. The physicochemical analysis revealed the following results for Sidr honey from Saudi Arabia and Egypt, respectively: a moisture content of 18.03 ± 0.05% and 19.03 ± 0.06%, EC values of 1.18 ± 0.05 and 1.16 ± 0.01 mS/cm, pH values of 4.87 ± 0.08 and 5.10 ± 0.01, FA of 37.50 ± 0.05 and 36.50 ± 0.05 meq/kg, total acidity of 41.06 ± 0.05 and 37.50 ± 0.05 meq/kg, lactone of 3.49 ± 0.005 and 1 ± 0.0 meq/kg, HMF of 20.92 ± 0.02 and 11.33 ± 0.01 mg/kg, and diastase of 59.97 ± 0.05 and 8.64 ± 0.06g/100 g. Honey from Saudi Arabia and Egypt displayed 22.51 ± 0.05 and 26.62 ± 0.16 % glucose, 40.33 ± 0.06 and 35.28 ± 0.01% fructose, 8.94 ± 0.17, and 8.87 ± 0.01% sucrose, and 8.22 ± 0.006 and 8.13 ± 0.01% maltose, respectively. According to the International Honey Commission (IHC) and GCC Standardization Organization (GSO) regulations, the levels of glucose, fructose, sucrose, and maltose were near the standard levels. Flavonoids, sugars, vitamins, and nitrogen contents were additionally measured using LC-MS/MS, whereas GC-MS was employed to identify aldehydes, ketones, phenols, acids, esters, anthraquinone, hydrocarbons, and nitrogenous compounds. The results of a study on the effect of honey’s geographic origin on its broad quality are summarized. As a result, knowing its optimal chemical and physical characteristics served as the criterion and indicator of the honey’s quality.